Health Financing Strategies In Fragile And Conflict-Affected Settings: Lessons From Humanitarian And Development Synergies - Muh Habibulloh; M. Munif (International Journal of Health Systems and Policy, 2025)
Health financing in fragile and conflict-affected settings (FCAS) presents complex challenges due to weak governance, insecure environments, and limited institutional capacity. Traditional financing mechanisms, which are often rigid and siloed, are inadequate for the dynamic needs of conflict zones. This study analyzes adaptive and hybrid financing models that integrate humanitarian assistance with long-term development approaches to support more resilient health systems. Drawing on case studies from South Sudan, Yemen, and the Democratic Republic of Congo, the analysis highlights the effectiveness of pooled funding, flexible donor strategies, joint planning platforms, and community engagement in improving health service delivery. Findings show that hybrid models are better suited to maintaining continuity, equity, and system responsiveness during protracted crises. Local ownership, especially through participatory planning and accountability mechanisms, is a key enabler of sustainability. However, challenges remain, including short funding cycles, fragmented coordination, and capacity limitations in financial and health information systems. Addressing these barriers requires a shift from isolated interventions toward integrated, inclusive, and long-term financing strategies. The study concludes that institutionalizing humanitarian-development synergies is essential for building adaptive, accountable, and equitable health systems in FCAS. These insights provide valuable guidance for donors, policymakers, and international agencies committed to improving health outcomes in complex emergency settings.